Pengaruh Ukuran Pemda Dan Tingkat Efisiensi Terhadap Opini Lkpd Studi Pada Pemerintahan Daerah Lampung - Silviana, Silviana; Saleh, Khaerul; Sukmawati, Fitri (Publikasi Indonesia, 2025)
Opinion LKPD Lampung still has not received a unqualified opinion in the 2015-2021 fiscal year period. The aim of the research is to test and analyze the influence of regional government size and level of efficiency on local financial statement opinions in the Lampung Regional Government.The observation population of the population in this study is all local governments in Lampung Province, there are 16 regional governments (districts and cities). The research uses secondary data, explanatory descriptive research using binary logistic regression analysis tools. The research period is from 2015 to 2021. The results of testing the first hypothesis show that regional government size has a positive effect on local financial statement opinion, meaning the hypothesis is accepted. The second hypothesis of the level of efficiency shows a negative influence, thus the hypothesis is rejected. Even though the size of the regional government is not large in terms of asset value, it does not necessarily mean that the local financial statement will not receive a unqualified opinion. the results of measuring the level of regional government efficiency concluded that it was not efficient, it does not necessarily mean that the local financial statement did not get a unqualifie opinion.